Diversification of COVID-19 Testing Resources to Decrease Racial/Ethnic Disparities: Comparative Use of Adaptive Approaches to Community Testing Across an Integrated Healthcare System - Jennifer S. Priem; Lisa M. Krinner; S. Tyler Constantine; Lewis McCurdy (Elsevier, 2022)
Background: Access to SARS-CoV-2 testing is a crucial component of early identification and disease containment. Racial and ethnic health disparities exist related to testing utilization. To optimize testing with limited resources, Atrium Health developed free-standing and roving testing centers outside of the traditional clinical settings in hopes of meeting the needs of a diverse urban community. The objective of this study is to evaluate differences in testing site utilization based on demographic factors, particularly race/ethnicity.Methods:A cohort study of patients tested for COVID-19 between March 10 and October 26, 2020, within the Atrium Health system.Results: 128,258 persons under investigation (PUIs) were tested across our health system, including 25,434 patients at our Mobile Integrated Health (previously called Community Paramedicine) drive-thru testing sites and community roving testing units. PUIs were on average 47 years old (SD = 17.7); approximately half were female and White/Caucasian. Drive-thru testing sites were utilized proportionally more by non-Hispanic Whites and African Americans, and less by Hispanic PUIs. Roving testing units were used significantly more by younger PUIs, Hispanics, and PUIs of other races/ethnicities.Conclusions: Diversification in testing site locations optimized testing resources, allowed for significant reduction in the burden of patient volumes, and avoided alteration of workflow in our urgent care facilities and Emergency Departments. Additionally, roving testing units may help to decrease racial/ethnic disparities in access to COVID-19 testing. Our results highlight the importance of offering a variety of testing modalities to reach different populations.